Prevalence of Nance Space Maintainer as a Treatment Modality among Children between the Age Group of 6-10 Years - Keerthiga Nagarajan (Institute of Medico-legal Publications Pvt Ltd, 2020)
The early loss of deciduous teeth may lead to a decrease in arch length and result in crowding, rotation,and impaction of the succedaneous teeth. Space management plays a pivotal role in preventing thesemalocclusions. This study aims to assess the prevalence of Nance space maintainers among childrenbetween the age group of 6-10 years in Chennai. A retrospective cross-sectional study was conducted usingthe patient records from June 2019 to April 2020, and children who underwent space maintainer therapywere selected by non-probability sampling. Data was collected and then subjected to statistical analysisusing Statistical Package for Social Science for Windows (version 20.0, SPSS Inc., Chicago Ill., USA). Theprevalence of nance space maintainer among 6-10 year old children was found to be 76.5%, with most ofthem being delivered to 8 year olds. More males than females underwent nance space maintainer therapy.53.85% of the 6-10 year olds receiving nance space maintenance therapy were found to be treated by thepost graduate students (p>0.05, statistically not significant). The prevalence of nance space maintainer as atreatment option among the mixed dentition phase in this study seems to be high when compared to otherstudies. Considering the limitations of the nance appliance, extensive research needs to be done to findalternatives to nance space maintainer therapy and to spread awareness among dentists on the necessity ofsuch further advancements.